Factors influencing Gen-Z customer perception online shopping in Indonesia - Rinto Syahdan (International Journal of Communication and Society, 2021)
This study aims to examine the relationship between benefits, ease of use, self-efficacy, safety, trust, and perceived usefulness on customer perceptions. The data in this study were collected through a survey. The samples in the study were consumers who made online purchases on Shoppee, Tokopedia, and Bukalapak, which amounted to 327 respondents. This study employed simple linear regression as a statistical and hypothetical test tool with the help of SPSS version 24. The conclusion of this study is that all hypotheses have a positive and significant effect on consumer perceptions and provide new findings that perceived usefulness is a variable that affects customer perceptions.